Architecture as a global system : scavengers, tribes, warlords and megafirms - Raisbeck, Peter (Emerald Publishing Limited, 2019)
Since the 1980s the architectural profession across the world has been driven by globalisation. The factors shaping this globalisation include neo-liberal economics, digital transformation and the rise of social media against the background of the profession's entrenched labour practices. In describing architecture as a global system, this book outlines how globalisation has shaped architecture and explores the degree to which architecture remains a distinct field of knowledge. The book identifies four categories of architects in this global system: scavengers, tribes, warlords and megafirms. By employing this institutional-logics approach, the author looks beyond the surface spectacle of iconic projects, celebrity architects and cycles of urban focused media outrage. From this perspective, the book illuminates the archipelagos and outposts of disciplinary knowledge that architectural actors traverse and highlights the frontiers at which architectural knowledge is both created and eroded. The author argues that to retain their future agency, architects must understand the contours and ecologies of practice that constitute this global system of architectural production. This book provides a clear-sighted analysis to suggest the points that need reconfiguring in this global system so that architects may yet shape and order the future of cities.
Includes index.
Keywords: Architecture and globalization.; Architecture -- General.; Theory of architecture.; elektronické knihy; electronic books